The Relationship between the Strategies of E-marketing mix and Marketing Effectiveness of the Palestinian Small Business Industrial Organizations in the City of Hebron - أبو فارة, يوسف (Journal of Economics and Administrative Sciences, 2020)
In the city of Hebron, small business industrial organizations face a major challenge related to its ability to reach, attract and sustain a sufficient number of customers in order to ensure its continuity and sustainability. The research problem is summarized in an attempt to reveal how the e-marketing could improve and support the marketing effectiveness of small business industrial organizations in the city of Hebron/Palestine. The importance of this research stems from the fact that it addresses a new knowledge branch of the field of marketing, which is electronic marketing for small business organizations, and the fact that the research highlights appropriate marketing solutions for these organizations in light of the Internet and its marketing uses, as it was found that this new tool carries solutions to this problem through extensive use of the electronic marketing mix strategies that give it a great marketing leverage, and gives it the opportunity to enter and access local, international and global markets that were not accessible except for large organizations. This research aims to identify the degree of use of electronic marketing in these organizations through the main strategies of the electronic marketing mix and to identify the degree of marketing effectiveness and highlight the role of electronic marketing in achieving the marketing effectiveness of these organizations. The research population consisted of 120 marketing managers in small business organizations in the industrial sector in the city of Hebron that adopt the electronic marketing of their products (through their websites or social media sites). The researcher used a simple random sample technique. The number of sample respondents is (92) managers. The questionnaire was distributed to each marketing manager. 84 questionnaires were retrieved, and this is considered a statistically acceptable recovery rate, this percentage reached about (89%).  In this research, the zero hypotheses, which stipulates that “there is no relationship between the electronic marketing mix strategies and the marketing effectiveness of small Palestinian business organizations in the industrial sector in Hebron”, was examined, in addition to examining the sub-hypotheses of the main hypothesis. The researcher used the descriptive approach due to its suitability to the nature of this research. A special questionnaire was designed to collect data from the respondents. The validity and reliability of the research tool (the questionnaire) were examined. A set of appropriate statistical tools were used, such as frequencies, percentages, standard deviations, t-test, Spearman correlation coefficient, and the Cronbach alpha.The results revealed that these small Palestinian business organizations adopt multiple aspects of the e-marketing mix strategies, which are the product strategy, pricing strategy, promotion strategy, distribution and website strategy, privacy strategy, and security strategy.This research reached a set of conclusions, the most important are the organizations' awareness of the importance of using e-marketing for their various products, and adopting this in their marketing strategy. The use of e-marketing for the products of small business organizations has multiple advantages related to the organization and customers, such as reducing marketing costs, increasing sales, displaying a large number of products online, and changing some negative trends of customers towards the products of these organizations.The research recommends these organizations to provide all the necessary requirements to achieve the continuous development and improvement of the applications of electronic marketing strategies in these organizations. The research recommends also to design and implement an electronic financial system for online payment.